Digoxin and Amiodarone on the Risk of Ischemic Stroke in Atrial Fibrillation: An Observational Study - Kuan-Cheng Lai; Sy-Jou Chen; Sy-Jou Chen; Chin-Sheng Lin; Fu-Chi Yang; Cheng-Li Lin; Cheng-Li Lin; Chin-Wang Hsu; Chin-Wang Hsu; Wen-Chen Huang; Wen-Chen Huang; Chia-Hung Kao; et al. (Frontiers Media S.A., 2018)
Purpose: The present study compared the risk of ischemic stroke in atrial fibrillation (AF) patients receiving digoxin and amiodarone.Methods: A retrospective cohort study was conducted using the longitudinal population-based database of Taiwan's National Health Insurance program. Patients with AF who received amiodarone or digoxin and were considered to have exposed to study drugs consecutively over 180 days during 2000-2010 were enrolled and divided into three groups: those who received amiodarone, digoxin, and amiodarone plus digoxin. All patients were followed from the index date to the occurrence of ischemic stroke, death, withdrawal from the insurance program, or December 31, 2011. Cox proportional hazard regression models were applied to determine the risk of ischemic stroke and associated risk factors.Results: The amiodarone, digoxin, and amiodarone plus digoxin cohorts comprised 797, 1419, and 376 patients, respectively. Overall, the patients who received digoxin (HR = 1.80; 95% CI = 1.41-2.31) or amiodarone plus digoxin (HR = 2.00; 95% CI = 1.49-2.68) had a higher risk of ischemic stroke, compared with those who received amiodarone. This risk was particularly at CHA2DS2VASc score of 2-5, but disappeared in those who received clopidogrel in the digoxin cohort. The risk of ischemic stroke in the amiodarone plus digoxin cohort did not differ significantly from that in the digoxin cohort (HR = 1.14; 95% CI = 0.90-1.44).Conclusion: Atrial fibrillation patients receiving digoxin are associated with a higher risk of ischemic stroke than are those receiving amiodarone. It is prudent to assess the stroke risk prior to applying treatment strategy for patients with AF.Strengths and Limitations of This Study          - This study is a population-based design with a completeness and accuracy of data, national coverage in both study and control cohorts. All insurance claims were double-checked by medical specialists for peer review.         - Information about serum levels of the drugs, coagulation status, and types of AF were unavailable in this administrative database.